Market-oriented grid and utility computing - Buyya, Rajkumar, 1970-; Bubendorfer, Kris. (Hoboken, N.J. : John Wiley & Sons, 2010)
The first single-source reference covering the state of the art in grid and utility computing economy research. This book presents the first integrated, single-source reference on market-oriented grid and utility computing. Divided into four main parts--and with contributions from a panel of experts in the field--it systematically and carefully explores:. Foundations --presents the fundamental concepts of market-oriented computing and the issues and challenges in allocating resources in a decentralized computing environment.;. Business models --covers business models for service providers and brokers supporting different types of distributed applications, as well as business rules-based models for managing virtual organizations and accounting operations and services in grid computing environments.; Policies and agreements --introduces policies, agreements, and specifications for the negotiation and establishment of contracts between providers and consumers. It also covers different approaches for resource allocation based on service-level agreements (SLAs) and management of risks associated with SLA violations.; Resource allocation and scheduling mechanisms --covers economic models, such as commodity models, reciprocation, auctions, and game theory, and middleware technologies, such as Nimrod/G and Gridbus, for market-oriented grid computing and utility-oriented resource allocation.
MARKET-ORIENTED GRID AND UTILITY COMPUTING; CONTENTS; CONTRIBUTORS; PREFACE; ACKNOWLEDGMENTS; ACRONYMS; PART I FOUNDATIONS; 1 Market-Oriented Computing and Global Grids: An Introduction; 2 Markets, Mechanisms, Games, and Their Implications in Grids; 3 Ownership and Decentralization Issues in Resource Allocation Mechanisms; 4 Utility Functions, Prices, and Negotiation; 5 Options and Commodity Markets for Computing Resources; PART II BUSINESS MODELS; 6 Grid Business Models, Evaluation, and Principles; 7 Grid Business Models for Brokers Executing SLA-Based Workflows; 8 A Business-Rules-Based Model to Manage Virtual Organizations in Collaborative Grid Environments; 9 Accounting as a Requirement for Market-Oriented Grid Computing; PART III POLICIES AND AGREEMENTS; 10 Service-Level Agreements (SLAs) in the Grid Environment; 11 SLAs, Negotiation, and Challenges; 12 SLA-Based Resource Management and Allocation; 13 Market-Based Resource Allocation for Differentiated Quality Service Levels; 14 Specification, Planning, and Execution of QoS-Aware Grid Workflows; 15 Risk Management In Grids; PART IV RESOURCE ALLOCATION AND SCHEDULING MECHANISMS; 16 A Reciprocation-Based Economy for Multiple Services in a Computational Grid; 17 The Nimrod/G Grid Resource Broker for Economics-Based Scheduling; 18 Techniques for Providing Hard Quality-of-Service Guarantees in Job Scheduling; 19 Deadline Budget-Based Scheduling of Workflows on Utility Grids; 20 Game-Theoretic Scheduling of Grid Computations; 21 Cooperative Game-Theory-Based Cost Optimization for Scientific Workflows; 22 Auction-Based Resource Allocation; 23 Two Auction-Based Resource Allocation Environments: Design and Experience; 24 Trust in Grid Resource Auctions; 25 Using Secure Auctions to Build a Distributed Metascheduler for the Grid; 26 The Gridbus Middleware for Market-Oriented Computing.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Computational grids (Computer systems); Utilities (Computer programs); Grilles informatiques; Utilitaires (Logiciels); COMPUTERS -- Client-Server Computing; Computational grids (Computer systems); Utilities (Computer programs)